Suboptimal monitoring and management in patients with unrecorded stage 3 chronic kidney disease in real-world settings: Insights from REVEAL-CKD - Tangri, Navdeep; Alvarez, Christian S.; Arnold, Matthew; Barone, Salvatore; Cebrián, Ana; Chen, Hungta; De Nicola, Luca; Järbrink, Krister; Kanumilli, Naresh; Lim, Kean Seng; Moriyama, Toshiki; Pecoits Filho, Roberto; et al. (European Journal of Clinical Investigation, 2024)
Background: Clinical practice guidelines for patients with chronic kidney disease (CKD) recommend regular monitoring and management of kidney function and CKD risk factors. However, the majority of patients with stage 3 CKD lack a diagnosis code, and data on the implementation of these recommendations in the real world are limited. Aim: To assess the implementation of guideline-directed monitoring and management practices in the real world in patients with stage 3 CKD without a recorded diagnosis code. Methods: REVEAL-CKD (NCT04847531) is a multinational, observational study of patients with stage 3 CKD. Eligible patients had ≥2 consecutive estimated glomerular filtration rate (eGFR) measurements indicative of stage 3 CKD recorded >90 and ≤730 days apart, lacked an International Classification of Diseases 9/10 diagnosis code corresponding to CKD any time before and up to 6 months after the second eGFR measurement. Testing of key measures of care quality were assessed. Results: The study included 435,971 patients from 9 countries. In all countries, the prevalence of urinary albumin–creatinine ratio and albuminuria testing was low. Angiotensin-converting enzyme inhibitor, angiotensin receptor blocker and statin prescriptions were highly variable, and sodium–glucose cotransporter-2 inhibitor prescriptions remained below 21%. Blood pressure measurements were recorded in 20.2%–89.9% of patients. Conclusions: Overall, a large proportion of patients with evidence of stage 3 CKD did not receive recommended, guideline-directed monitoring and management. The variability in standard of care among countries demonstrates a clear opportunity to improve monitoring and management of these patients, most likely improving long-term outcomes.
CRIS-Team Scopus Importer:2024-07-26
Keywords: chronic kidney disease; clinical guidelines; management; monitoring; real-world